Principles of Ecology Revisited: Integrating Information and Ecological Theories for a More Unified Science - O'Connor, Mary I.; Pennell, Matthew W.; Altermatt, Florian; Matthews, Blake; Melián, Carlos J.; Gonzalez, Andrew (Frontiers in Ecology and Evolution, 2019)
The persistence of ecological systems in changing environments requires energy, materials and information. Although the importance of information to ecological function has been widely recognized, the fundamental principles of ecological science as commonly expressed do not reflect this central role of information processing. We articulate five fundamental principles of ecology that integrate information with energy and material constraints across scales of organization in living systems. We show how these principles outline new theoretical and empirical research challenges, and offer one novel attempt to incorporate them in a theoretical model. To provide adequate background for the principles, we review major concepts and identify common themes and key differences in information theories spanning physics, biology and semiotics. We structured our review around a series of questions about the role information may play in ecological systems: i) what is information? ii) how is information related to uncertainty? iii) what is information processing? iv) does information processing link ecological systems across scales? We highlight two aspects of information that capture its dual roles: syntactic information defining the processes that encode, filter and process information stored in biological structure and semiotic information associated with structures and their context. We argue that the principles of information in living systems promote a unified approach to understanding living systems in terms of first principles of biology and physics, and promote much needed theoretical and empirical advances in ecological research to unify understanding across disciplines and scales.